Analisa Struktur Mikro Pada Baja S35C Akibat Variasi Posisi Pengelasan SMAW - Mokhammad Nursalim (Jurnal Teknik Mesin, 2019)
Progress in the field of welding technology is a technique of using metal welding because of the existence of buildings and machinery made using welding techniques. The method used in this study was experimental, and this study used S35C low carbon steel with the composition: C = 0.32-0.38 Si = 0.15-0.35 Mn = 0.60-0.90 P = 0.030 S = 0.035. 2G, 3G and 4G, from the results of this study in terms of calculations from the proportion test, the white color comparison 2G with 3G Fhitung −1.38 > Ftabel -1, 64, the proportion of white 2G with 4G Fhitung -1.60 > Ftabel - 1.64, the proportion of 3G white color with 4G F count -1.51> Ftable- 1.64, the proportion of black color is 2G with 3G Fhitung -3.49 > Ftabel - 1.64, the proportion of black is 2G with 4G Fhitung -1,60 > Ftabel - 1.64, it can be set aside from the comparison of white and black between the variations of 2G, 3G, 4G, there is no difference, and also from the trials of white and black f, the results of Fhitung 0.39 < Ftabel 3,35 it is concluded that the white and black microstructure of welding position 2G, 3G and 4G is no different.